Feeding behaviour of Tilapia (Oreochromis sp.) fingerlings to microbeads - Chua, Chiew Peng; Mohamat Yusuff, Ferdaus (2019)
We examined the behavior in response to food- and non-food particles, mortality and gut contents of Oreochromis sp. fingerlings exposed for 96 hours to microbeads extracted from a body scrub, which is a mixture of two types of beads, one positively buoyant, green in color, and larger than the other, which is negatively buoyant and whitish. These were termed green (GB) and white beads (WB), respectively. The exposure was done under four different conditions: Tank A, with microbeads only; Tank B, with microbeads and normal food pellets; Tank C, with normal food pellets followed by microbeads; Control Tank, normal food pellets only. Each tank was placed with four fingerlings, 4.0-5.3 cm in total length, and the experiment was duplicated. The water parameters of all tanks were controlled and monitored at DO > 1 mg/L, pH = 6 – 9, temperature = 29 –31 °C. Behavioral response toward microbeads indicated that fingerlings attempted to consume the microbeads intentionally with the absence of food, or accidentally consumed the microbeads in the presence of food. The number of the GB in the gut was 3–66 in Tank A, followed by Tank B (2–29) and Tank C (2–5). The mortality of these fingerlings due to feeding on the microbeads was not confirmed as fatality was also recorded in the control tank, as well as in the experimental tanks.